Hackerteen. - Marques, Marcelo (O'Reilly Media, Inc., 2008)
Yago is a computer whiz and is enrolled in HackerTeen where he learns the internet ethics. However, criminals want to use his knowledge for their gain and he is tricked into staging an attack on the world's 13 root dns servers.